2017
DOI: 10.1007/s11356-017-8920-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertility and abiotic stresses management in cotton crop: a review

Abstract: This review outlines nitrogen (N) responses in crop production and potential management decisions to ameliorate abiotic stresses for better crop production. N is a primary constituent of the nucleotides and proteins that are essential for life. Production and application of N fertilizers consume huge amounts of energy, and excess is detrimental to the environment. Therefore, increasing plant N use efficiency (NUE) is important for the development of sustainable agriculture. NUE has a key role in crop yield and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 149 publications
3
84
1
Order By: Relevance
“…Moreover, in support of the outcomes of the present study, several other scholars reported that co-application of nitrogen significantly boosted the level of antioxidant enzymes in soybean [56], Catharanthus roseus [57], and blueberry [58]. Nitrogen serves as a first line of defense against internal and environmental oxidative stressors [17,21,59,60]. Moreover, the positive effect of nitrogen may be related to nitrogen being an effective component of antioxidant enzymes and antioxidants [17,27].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, in support of the outcomes of the present study, several other scholars reported that co-application of nitrogen significantly boosted the level of antioxidant enzymes in soybean [56], Catharanthus roseus [57], and blueberry [58]. Nitrogen serves as a first line of defense against internal and environmental oxidative stressors [17,21,59,60]. Moreover, the positive effect of nitrogen may be related to nitrogen being an effective component of antioxidant enzymes and antioxidants [17,27].…”
Section: Discussionsupporting
confidence: 87%
“…Deficit irrigation results in deeper root penetration of the cotton plant (Sampathkumar et al, 2013), which can conserve 22% of the soil water (Mustafa et al, 2011). Nitrogen application to a cotton crop especially in a water deficit is essential to recover growth and development from drought stress (Khan et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that salinity can cause crop yield losses even though the effects of salinity may not be obvious. Both salt tolerance and sensitivity of a specific crop depend on its ability to extract water and nutrients from saline soils and to avoid excessive tissue accumulation of salt ions (Ahmad et al 2017;Khan et al 2017;Kaleem et al 2018) The majority of vegetable crops is highly salt sensitive. In the model of Maas & Hoffman (1977), relative crop yield is not affected until a salinity threshold (ECt) is exceeded, according to the following equation: Y = 100 -S (EC e -EC t ), where Y is the relative crop yield with 100 being the maximum yield, EC e is the salinity of saturated soil extract, and EC t (dS m À1 ) is the threshold defined as the value of the electrical conductivity (EC) that is expected to cause the initial significant reduction in the maximum expected yield, and S is the slope that represents the percentage of yield expected to be reduced for each unit of added salinity above the EC t .…”
Section: Salinity Induces Decline Of Biomass and Yield Lossesmentioning
confidence: 99%